Klasika, balkanistika, paleoslavistika : materijali od nauçniot sobir po povod odbelejuvanjeto na 85-godişninata od raganjeto i 60 godini nauçna rabota na akademik Petar Hr. Ilievski = Classical, Balkan and Paleoslavic studies : proceedings of the scientific conference held in honour of academician Petar Hr. Ilievski on the occasion of his 85th birthay and 60 years of scientific activity. (Skopje)
444 s.